Analysis of the level of regional financial independence in cities in South Sumatra Province - Maryanti Sunami; Siti Hodijah; Parmadi Parmadi (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study aims to analyze the level of regional financial independence and examine differences among cities in South Sumatra Province during the 2020–2024 period. The study employs a quantitative method with a comparative descriptive approach using secondary data obtained from regional budget realization reports. Data analysis was conducted by calculating the regional financial independence ratio and testing hypotheses using the One-Way ANOVA test. The results indicate significant differences in the level of regional financial independence among the cities. Palembang recorded the highest average independence ratio of 67.03 percent and was categorized as participatory, while Prabumulih, Pagar Alam, and Lubuklinggau recorded ratios of 12.10 percent, 11.43 percent, and 14.91 percent, respectively, which were categorized as instructive. Furthermore, the statistical test produced a significance value below 0.05, indicating significant differences in regional financial independence among cities in South Sumatra Province